ADSORÇÃO DE COMPOSTOS FENÓLICOS EM CARVÃO ATIVADO PREPARADO A PARTIR DO AGUAPÉ (Eichhornia crassipes) - Barbosa, Charles Silva (2013)
Activated carbon was produced from the water hyacinth (CAA) by impregnation with ZnCl₂ (1:2), followed by pyrolysis at 700 °C, under N₂, and presented a surface area of 640.4 m²gˉ¹. We ve done kinetics tests, equilibrium and thermodynamics tests, and also tests to verify the influence of pH, temperature and initial concentration on adsorption process, using the following phenolic compounds: fenol, o cresol and m cresol. The pHzpc value of CAA was estimated at 5.4. Kinetic studies were performed at pH 10 due to the greater efficiency of removal of phenolic compounds. The kinetic models of pseudo-first and second orders were applied at temperatures 10, 25, 35 and 45°C, and the second order model (R² ≥ 0.94) was that best modeled the experimental data. The adsorption isotherms were obtained by varying the phenolic compounds concentration in the range from 150 to 1000 mg Lˉ¹. The Freundlich and Langmuir adsorption isotherms models have been applied to fit the experimental data, and the Freundlich model was the best one. The maximum quantity adsorbed of each compound, obtained from Langmuir, at 45 oC followed the order: fenol (163.7 mg gˉ¹) > o-cresol (142.3 mg gˉ¹) > m-cresol (130.2 mg gˉ¹). The thermodynamic parameters confirmed the spontaneity of the adsorptive processes, which are endothermic, but with increasing entropy.